Effect of genotype on physico-chemical characteristics of rabbit meat - Belichovska Daniela, Belichovska Katerina, Pejkovski Zlatko, Uzunoska Zora (Insitute of Meat Hygiene and Technology, Belgrade, 2017)
Basic chemical composition (water, protein, fat, ash), water holding capacity and cooking loss of rabbit meat (Oryctolagus cuniculus) were investigated. The meat originated from three diff erent genotypes (New Zealand White, Californian and crossbred animals of these two breeds). Animals up to 30 days old fed exclusively on their mother’s milk and then received commercial feed ad libitum until they were 90 days old. Before slaughter, rabbits had an average live weight of 2038.17 g. Muscles from the hind legs from 21 animals (7 of each genotype) were taken for examination at 48 h post mortem. Chemical composition was determined according to standard methods. Water holding capacity was determined by the Grau-Hamm fi lter paper press method. Cooking losses were measured by dipping 10 g meat pieces into boiling water for 10 minutes, as well as by roasting chops in an electric oven at 180°C to an internal temperature of 78 °C. On average, rabbit meat contained 74.49% water, 21.79% protein, 2.78% fat, 1.24% ash and its energy value was 494.79 kJ 100g-1. Genotype had no signifi cant eff ect on chemical composition or water holding capacity of meat. The content of free water in the meat amounted, on average, to 52.28% and bound water content was 22.21%. Cooking loss was signifi cantly (P<0.05) lower in meat from crossbreds. During boiling, the meat, on average, lost 32.73% of its weight, compared with a 38.11% loss during roasting
Keywords: rabbit meat, chemical composition, water holding capacity, cooking loss